2001
DOI: 10.1002/jmv.2090
|View full text |Cite
|
Sign up to set email alerts
|

Isolated anti‐HBc in chronic hepatitis C predicts a poor response to interferon treatment

Abstract: The sustained response to interferon-alpha treatment was evaluated in 147 anti-HCV/HCV-RNA-positive, HBsAg-negative, chronic hepatitis patients, according to HCV genotypes and the presence or absence of anti-HBs and anti-HBc. These patients had been included in a controlled study on the safety, tolerability, and efficacy of three types of interferon-alpha given at a dose of 3 MU three times weekly for 52 weeks. One hundred and two patients had HCV genotype 1, 42 a non-1 HCV genotype and 3 multiple HCV genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 50 publications
2
27
2
Order By: Relevance
“…OBI may be observed in the window period of acute HBV infection [16] in blood donors and in recipients of blood and blood products [9,17,18] , in patients with HCV chronic infection [7,19] , in cryptogenic chronic hepatitis, in patients under pharmacological suppression of the immune system [20,21] and in those with immunodepression due to HIV infection; it has also been associated to the development of hepatocellular carcinoma [22][23][24][25][26][27][28][29][30] . It has been shown that the hepatitis B virus maintains its pro-oncogenic properties in OBI [31] and that its presence in patients with chronic hepatitis C is associated with a higher risk of disease progression and HCC development [32][33][34][35][36] and with a reduced response to alfa interferon treatment [37][38][39] . The clinical importance of OBI is also underscored by the need for nucleot(s)ide treatment to prevent the recurrence of HBV infection in HBsAgnegative/anti-HBc-positive patients in various immunosuppressive settings [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…OBI may be observed in the window period of acute HBV infection [16] in blood donors and in recipients of blood and blood products [9,17,18] , in patients with HCV chronic infection [7,19] , in cryptogenic chronic hepatitis, in patients under pharmacological suppression of the immune system [20,21] and in those with immunodepression due to HIV infection; it has also been associated to the development of hepatocellular carcinoma [22][23][24][25][26][27][28][29][30] . It has been shown that the hepatitis B virus maintains its pro-oncogenic properties in OBI [31] and that its presence in patients with chronic hepatitis C is associated with a higher risk of disease progression and HCC development [32][33][34][35][36] and with a reduced response to alfa interferon treatment [37][38][39] . The clinical importance of OBI is also underscored by the need for nucleot(s)ide treatment to prevent the recurrence of HBV infection in HBsAgnegative/anti-HBc-positive patients in various immunosuppressive settings [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Instead, very little is known about HBV/HCV acute concurrent infection because only a few case reports are available in the literature. 11,12 Also, little is known about HBV acute infection when it develops in chronic HCV carriers, but the few case reports published on the topic suggest an association with a severe clinical presentation.…”
mentioning
confidence: 99%
“…In particular, Mason et al [1998] demonstrated that HBV may persist for years in the liver of HBsAg negative patients with previous acute HBV infection, since they found both HBV transcription and an intact direct repeat region of HBV-DNA in the liver of patients 3-67 months after the acute hepatitis B infection. The peculiar coinfection of the patients in Case bC group seems to be characterized by a more severe clinical presentation [Cacciola et al, 1999;Sagnelli et al, 2001a] and a poor response to a-interferon treatment [Zignego et al, 1997;Sagnelli et al, 2001b], but no data on liver histology are available so far. In the present study all patients with HCV-related chronic hepatitis with circulating anti-HBc were included in Case bC, whether a silent HBV infection was demonstrated (HBV-DNA detectable in plasma) or not.…”
Section: Discussionmentioning
confidence: 97%